Impact of Integration of FO Membranes into a Granular Biomass AnMBR for Water Reuse - Pere Olives; Lucie Sanchez; Geoffroy Lesage; Marc Héran; Ignasi Rodriguez-Roda; Gaetan Blandin (Membranes, 2023)
The granular sludge based anaerobic membrane bioreactor (G-AnMBR) has gained emphasis in the last decade by combining AnMBR advantages (high quality permeate and biogas production towards energy positive treatment) and benefits of granular biomass (boosted biological activity and reduced membrane fouling). With the aim to further reduce energy costs, produce higher quality effluent for water reuse applications and improve system efficiency, a forward osmosis (FO) system was integrated into a 17 L G-AnMBR pilot. Plate and frame microfiltration modules were step by step replaced by submerged FO ones, synthetic wastewater was used as feed (chemical oxygen demand (COD) content 500 mg/L), with hydraulic retention time of 10 h and operated at 25 °C. The system was fed with granular biomass and after the acclimation period, operated neither with gas sparging nor relaxation at around 5 L.m−2.h−1 permeation flux during at least 10 days for each tested configuration. Process stability, impact of salinity on biomass, the produced water quality and organic matter removal efficiency were assessed and compared for the system working with 100% microfiltration (MF), 70% MF/30% FO, 50% MF/50% FO and 10% MF/90% FO, respectively. Increasing the FO share in the reactor led to salinity increase and to enhanced fouling propensity probably due to salinity shock on the active biomass, releasing extracellular polymeric substances (EPS) in the mixed liquor. However, above 90% COD degradation was observed for all configurations with a remaining COD content below 50 mg/L and below the detection limit for MF and FO permeates, respectively. FO membranes also proved to be less prone to fouling in comparison with MF ones. Complete salt mass balance demonstrated that major salinity increase in the reactor was due to reverse salt passage from the draw solution but also that salts from the feed solution could migrate to the draw solution. While FO membranes allow for full rejection and very high permeate purity, operation of G-AnMBR with FO membranes only is not recommended since MF presence acts as a purge and allows for reactor salinity stabilization.